Bimbingan Teknis Penerapan Teknologi Perbanyakan Tanaman Melati di Sentra Pengembangan Bunga Kabupaten Banjar - Hilda Susanti; Indriani Indriani; Ronaldo Harianto (Universitas Lambung Mangkurat, 2023)
Community service activities in the form of technical guidance on the application of jasmine plant propagation technology have been carried out in Jingah Habang Ilir Village, Karang Intan District, Banjar Regency, South Kalimantan on Thursday, September 23, 2021. The technical guidance activity aims to provide training to farmers on jasmine plant propagation technology based on GAP, increasing the production and productivity of jasmine in the flower development center of Banjar Regency, as well as assisting the Regional Government in making policies regarding the flower development center of Banjar Regency. There were 34 participants who attended, consisting of farmers producing jasmine and PKK cadres from five villages, namely Jingah Habang Ilir, Karang Intan, Pandak Daun, Bincau, and Labuan Tabu. The problems found at the producer farmer level are that farmers do not understand the nursery management in the form of the number of cuttings planted in nursery polybags and enclosures, farmers do not understand about the types of pests that attack jasmine plants and their control, and farmers have not received training in the form of theory and practice of plant propagation directly in the field. The solution offered to answer the problem of jasmine propagation in five jasmine-producing villages in Banjar Regency is the need for comprehensive training on jasmine cultivation, support for nursery infrastructure and facilities, monitoring and evaluation on an ongoing basis.